SOCIOLOGICAL PERSPECTIVES ON EDUCATIONAL INEQUALITY: A SYSTEMATIC LITERATURE REVIEW OF SOCIAL STRATIFICATION, CULTURAL CAPITAL, AND ACCESS TO LEARNING OPPORTUNITIES - Hikmat (GoAcademica Research dan Publishing, 2023)
Educational inequality has long been a central concern in sociological inquiry, as it reflects the persistent disparities in access to resources, opportunities, and outcomes across social groups. This study conducts a systematic literature review to examine how sociological perspectives illuminate the mechanisms through which social stratification and cultural capital shape unequal educational trajectories. By synthesizing findings from diverse academic sources, the review highlights the multidimensional nature of inequality that extends beyond economic resources to include symbolic and cultural assets. The analysis draws extensively on Bourdieu’s theory of cultural capital, demonstrating how family background, linguistic practices, and cultural exposure reinforce social hierarchies in education. Moreover, the review underscores that access to learning opportunities remains unequally distributed across class, gender, and geographic lines. Existing studies consistently reveal that institutional structures often reproduce, rather than mitigate, social inequalities in education. The findings suggest that educational inequality is not merely a reflection of individual shortcomings but a structural issue embedded within broader social dynamics. In synthesizing these perspectives, this article contributes to a deeper theoretical understanding of how inequality persists within education systems. The review also identifies critical gaps in the literature, including limited comparative studies across contexts and insufficient attention to intersectionality. Ultimately, the study provides theoretical insights and policy-relevant implications for addressing educational inequality from a sociological standpoint.